2015
DOI: 10.1186/s12937-015-0048-6
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the parenteral dose of fish oil supplementation and the variation of liver function tests in hospitalized adult patients

Abstract: BackgroundHepatic dysfunction is a complication associated with parenteral nutrition (PN). Our primary objective was to study the relationship between doses of intravenous fish oil (FO) emulsion in PN and the variation in the main liver function tests (LFTs) in hospitalized PN-treated adults. As a secondary objective, we studied the safety of FO administration.MethodsWe conducted a retrospective study in adult patients receiving FO supplementation in PN. Demographic, nutritional and safety variables were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…In addition, EPA reduces levels of TNF-a and IL-6 in the hepatocytes 32 ,and DHA improves hepatic injuries induced by valproate through reforming of oxidative stresses and inflammation without having any effect on plasma level of valproate 33 .Moreover, it has been shown that addition of fish oil supplement to parental diet reforms the increased levels of hepatic enzymes resulted from hepatic mal-function related to parental nutrition 34 .Studies have shown that 10% fish oil and 1 g% artichoke leaf can restore hepatocellular carcinoma in rats 35 . Lee et al (2008) determined that Omega-3 fatty acid can repair hepatocellular damage caused by obstruction of the bile ducts 36 ; it was also shown that fish oil along with allopurinol And verapamil improve hepatic injuries resulting from ischemia by a significant reduction in oxidative stress and hepatic enzymes 37 .In a study by Mardones et al (2012), it was demonstrated that combination of thyroid hormone and fish oil protocol prevents liver damage resulted from tissue injury and ischemia 38 .Furthermore, Omega-3 fatty acid prevents acute liver defects and stimulates liver regeneration following 90% hepatectomy in rats 39 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, EPA reduces levels of TNF-a and IL-6 in the hepatocytes 32 ,and DHA improves hepatic injuries induced by valproate through reforming of oxidative stresses and inflammation without having any effect on plasma level of valproate 33 .Moreover, it has been shown that addition of fish oil supplement to parental diet reforms the increased levels of hepatic enzymes resulted from hepatic mal-function related to parental nutrition 34 .Studies have shown that 10% fish oil and 1 g% artichoke leaf can restore hepatocellular carcinoma in rats 35 . Lee et al (2008) determined that Omega-3 fatty acid can repair hepatocellular damage caused by obstruction of the bile ducts 36 ; it was also shown that fish oil along with allopurinol And verapamil improve hepatic injuries resulting from ischemia by a significant reduction in oxidative stress and hepatic enzymes 37 .In a study by Mardones et al (2012), it was demonstrated that combination of thyroid hormone and fish oil protocol prevents liver damage resulted from tissue injury and ischemia 38 .Furthermore, Omega-3 fatty acid prevents acute liver defects and stimulates liver regeneration following 90% hepatectomy in rats 39 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, EPA reduces levels of TNF-a and IL-6 in the hepatocytes [33], and DHA improves hepatic injuries induced by valproate through reforming of oxidative stresses and inflammation without having any effect on plasma level of valproate [34]. Moreover, it has been shown that addition of fish oil supplement to parental diet reforms the increased levels of hepatic enzymes resulted from hepatic mal-function related to parental nutrition [35]. Studies have shown that 10% fish oil and 1 g% artichoke leaf can restore hepatocellular carcinoma in rats [36].…”
Section: Discussionmentioning
confidence: 99%